Sclerotinia stem rot caused by Sclerotinia Sclerotiorum on soybeans in Nigeria - Akem, C.N.; Dashiell, Kenton E. (Scientific Societies, 1992)
In Aug. 1990, S. sclerotiorum was isolated from soyabean cultivars TGx 1440-1E and TGx 1627-3F at Bukuru, Plateau, Nigeria. Disease symptoms are described. This is the first report of Sclerotinia stem rot of soyabean in Nigeria and West Africa.